Transnational mobility through education: a Bourdieusian insight on life as middle transnationals in Australia and Canada. (15th March 2018) - Soong, Hannah; Stahl, Garth; Shan, Hongxia
ABSTRACT: This article argues for a more nuanced view of mobility through education within an era of increased globalisation. We explore questions of transnational mobility through the lens of underexplored Bourdieusian concepts, specifically transnational habitus and habitus clivé. Our analysis shows how one's perception of a 'better life' and one's ideology of 'entrepreneur self' are produced despite one's encounter with disparity between their fields of their host countries and countries of origin. We therefore assert the need for a more complex conceptual work to unpack the lived experience of mobility especially for those who are unable to operationalise their capital in the transnational field.